2013
DOI: 10.5137/1019-5149.jtn.8551-13.0
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 in the ventricular cerebrospinal fluid correlated with the prognosis of traumatic brain injury

Abstract: AIm: Matrix metalloproteinase 9 (MMP-9) has been shown to be a potential biomarker for outcome prediction after neuron damage. This study investigated whether MMP-9 could be used for outcome prediction after traumatic brain injury (TBI). mATERIAL and mETHods: For the TBI group, cerebrospinal fluid (CSF) was collected at different days after surgery from 6 head injury patients who had received surgical intervention with external ventricular drainage insertion. CSF collected from non-TBI patients (N=85) diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…MMP-9 is expressed in normal adult brain and is also elevated in response to TBI (Hadass et al, 2013;Hayashi et al, 2009). In humans, TBI is also associated with rapid increase of increased MMP-9 in brain parenchyma (Guilfoyle et al, 2015), cerebrospinal fluid (Liu, Chen, Lee, & Cho, 2014), and plasma (Copin et al, 2012) and, which may be used for the prognosis of severity and outcome of injury (DeFazio et al, 2014;Vilalta et al, 2008).…”
Section: A Tr I X M E Ta Ll Op Rote I Na S E S ( Mm P S)mentioning
confidence: 99%
“…MMP-9 is expressed in normal adult brain and is also elevated in response to TBI (Hadass et al, 2013;Hayashi et al, 2009). In humans, TBI is also associated with rapid increase of increased MMP-9 in brain parenchyma (Guilfoyle et al, 2015), cerebrospinal fluid (Liu, Chen, Lee, & Cho, 2014), and plasma (Copin et al, 2012) and, which may be used for the prognosis of severity and outcome of injury (DeFazio et al, 2014;Vilalta et al, 2008).…”
Section: A Tr I X M E Ta Ll Op Rote I Na S E S ( Mm P S)mentioning
confidence: 99%
“…Several studies have found that MMPs and VEGF were increased in the blood and cerebrospinal fluid (CSF) of patients with traumatic brain injury (TBI), but were significantly decreased over time. [25][26][27] Our patients were seen > 21 days after injury; therefore, the impact of elevations in MMPs/VEGF occurring in TBI patients on the research is limited. Several studies have reported that the concentration of VEGF was higher in hematoma fluid than in serum in CSDH patients.…”
Section: Mmp-2 Mmp-9 and Vegf In The Development Of Csdhmentioning
confidence: 99%
“…MMP9 is released from astrocytes, neurons and microglia as well as leukocytes and macrophages as an inactive proprotein, which is then activated by extracellular proteinases. MMP9 has been shown to be a potential biomarker for outcome prediction after neuron damage [ 14 ], and is particularly induced in neuronal lesions and cerebral ischemia [ 16 ]. Moreover, MMP9 might be important in remyelination processes as it facilitates oligodendrocyte regrowth [ 17 ].…”
Section: Introductionmentioning
confidence: 99%